Microstructural and magnetic properties of Yttrium Iron Garnet derived from steel waste product - Mohd Shahrani, Nuraine Mariana (2016)
In this research work, the morphology and magnetic properties-evolutions in Yttrium Iron Garnet (YIG) were studied in details, focusing on parallel evolving relationship with their dependences on sintering temperature. The iron oxide that has been used to synthesize YIG was obtained from the steel waste product, mill scale. There is less study and no reports published regarding the evolution of microstructure and magnetic properties YIG from low sintering temperature to high sintering temperature by mill scale waste product. The raw mill scale went through the milling and purification process by magnetic and non-magnetic separation and curie temperature separation technique to produce high purity iron oxide powder as main raw material in preparing YIG and fabricate YIG by high energy ball milling process. The obtain iron oxide was characterized by X-ray Diffractometer (XRD), X-ray fluorescence (XRF), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy for mineralogical composition and chemical analysis. The results of XRD indicated that the synthesized iron oxide identified as a α-Fe2O3 (hematite). Moreover, XRF, XPS, FTIR and Raman data was found to correspond with pure hematite. Among the characterization procedures, the highlight properties were phase identification by XRD, microstructure by FESEM, magnetic permeability by impedance material analyzer and saturation magnetization by VSM. The XRD pattern of YIG showed an improvement of crystallinity with increasing sintering temperature. Full YIG phase was seen for samples sintered at 1100oC and upwards. The temperature obtain of YIG fabricate is comparable with high energy milling method by commercial iron oxide raw material. FESEM micrographs showed larger grains as the sintering temperature increased, and the amounts of porosity were decreased, as the some grains grew at the expense of others. The initial permeability, showed the highest value of 51.70o at 1400oC, and decrement values of initial permeability at 700oC to 800oC because of the presence of weak ferromagnetic phases. The results of VSM showed an increasing tendency of saturation magnetization, with increased grain sizes, and the decrement value for samples sintering at 700oC to 800oC. These results can be associated with the formation of weak ferromagnetic behavior of α-Fe2O3 and YFeO3 phases. A particular pattern of the magnetic properties with sintering temperature is a manifestation of the phase purity level and microstructural factors. Thus, three groups of ferromagnetic behavior of YIG can be classified based on those factors.